STRATEGI PEMBELAJARAN TAHFIDZ DALAM RANGKA MEWUJUDKAN VISI QUR'ANI DI SEKOLAH ISLAM TERPADU SALSABILA GROUP - Hozaimi; Nia Kurniasari (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Tahfidz Al-Qur'an learning is one of the essential components in the integrated Islamic education system, aimed at shaping a generation with a Qur'anic character. This study aims to describe the Tahfidz learning strategy in realizing the Qur'anic vision at the Integrated Islamic School of the Salsabila Islamic Education Institute. This research employs a qualitative descriptive approach. Data were collected through participatory observation, interviews, and documentation review. Data analysis followed an interactive model encompassing data collection, data reduction, data presentation, and conclusion drawing. The findings reveal that Tahfidz Al-Qur'an learning receives special attention at the school. Learning is conducted through various methods, including halaqoh, sorogan, talaqqi, independent learning, rhythm-based learning, Tahfidz House, and the presentation of learning achievements. To support more effective learning outcomes, the school also implements a parent involvement program. The Al-Qur'an Olympiad (OLIQ) serves as a competitive event among students across all SIT Salsabila units. Scheduling study sessions at the beginning of lessons, muroja'ah practice, and the use of specialized learning media further support students in achieving their memorization targets. The Tahfidz learning strategy implemented at SIT Salsabila has proven effective in realizing the Qur'anic vision, demonstrating that a school's vision can genuinely shape its graduate profile. These findings are expected to serve as a valuable reference for other Islamic educational institutions in designing and developing more effective and structured Tahfidz learning strategies